ALUMINIUM BRONZE. NANOSTRUCTURAL PROCESSES OF MELTING AND MOULDING - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия, 2018)
It is shown that melting and molding of aluminum bronze are difficult physical and chemical processes. In them the major role is played by the centers of crystallization of dendrites of a a-phase, the a-phase nanocrystals dissolved and the adsorbed oxygen and hydrogen. The role of the modifying crystals of an intermetallid of ZrAl3 is reduced to reduction of concentration of the dissolved oxygen and hydrogen and an intensifi ation of process of coagulation of nanocrystals of a a-phase in the centers of crystallization of dendrites of a a-phase.